SEKRESI INTERLEUKIN-8 (IL-8) DAN HUBUNGANNYA DENGAN TINGKAT KEPARAHAN PENYAKIT INFEKSI DENGUE - Wihandani, DM; Ayu Dewi, NN; Somia, Agus (journal of internal medicine, 2009)
Elevation of IL-8 was found in many viral infection include dengue infection and related to the increases of illnessgradation. The aim of study is to know the secretion of IL-8 and the relation with the severity of the disease that caused by dengueviral infection that hospitalized at Sanglah hospital. There were 58 patients that diagnosed with dengue haemorrhagic fever basedon WHO criterion. Those samples consist of 38 patients of DHF grade I (mild) and 20 patients of DHF grade II, III and IV(severe). Serum was taken and then the level of IL-8 was examined by ELISA method with microplate reader in 450 nm wavelength (bioMerieux Reader 250). The data was analize statistically with non parametric measurement. The result showed thatthere were significant differences of IL-8 level between healthy people (control) and samples, and between mild and severepatients. We conclude that increase of IL-8 level related to severity of dengue viral infection